ANALISIS STRATEGI PEMASARAN SYARIAH PADA PRODUK MITRA EMAS DI BANK JABAR BANTEN SYARIAH KCP CIKURUBUK - Ana Herlina; Dede Husni Mubarok; Helmi Maulana (Syari'ah Economics, 2019)
This study aims (1) to determine the marketing strategy of gold partner products at Bank Jabar Banten Syariah KCP Cikurubuk Tasikmalaya; (2) to find out the SWOT analysis in determining the marketing strategy at BJB Syariah KCP Cikurubuk; and (3) to find out how the marketing strategy is to increase sales of gold partner products at BJB Syariah KCP Cikurubuk. This qualitative research uses a descriptive qualitative approach that produces descriptive data in the form of written or spoken words from people or observable behaviors that are carried out in case studies with observations, interviews, and documentation. The results of the study illustrate that the marketing strategy used by Bank BJB Syariah KCP Cikurubuk is the marketing mix or called the marketing mix which includes product, price, service, location and promotion strategies. So with this marketing mix, Bank BJB Syariah has experienced an increase in customers from the previous year, this is evidenced by data obtained by researchers from Bank BJB Syariah KCP Cikurubuk, but the increase experienced is still less significant because many competing institutions also have the same advantages and lack maximum of Bank BJB Syariah KCP Cikurubuk in implementing the marketing strategy that has been implemented. The SWOT analysis determines the marketing strategy for the gold partner product that has been implemented by Bank BJB Syariah KCP Cikurubuk has helped Bank BJB Syariah itself in analyzing various threats, opportunities, weaknesses, and strengths. So that Bank BJB Syariah KCP Cikurubuk can analyze market conditions significantly.